2004
DOI: 10.1038/sj.bmt.1704670
|View full text |Cite
|
Sign up to set email alerts
|

Donor lymphocyte infusions for multiple myeloma: clinical results and novel perspectives

Abstract: Summary:Donor lymphocyte infusions (DLIs) provide effective therapy for patients with various hematological malignancies who have relapsed after allogeneic hematopoietic stem cell transplantation (HSCT). In patients with multiple myeloma (MM), DLIs can induce response rates of 40-52%. DLIs were employed as treatment for MM relapse or as prophylaxis for relapse in MM patients undergoing allo-HSCT. The clinically most relevant treatment-related morbidity with DLIs is the occurrence of graft-versus-host disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…In addition, several of the relapses presented at unusual extramedullary sites, a phenomenon described before in conjunction with DLI. [35][36][37][38][39] Together, these observations are compatible with the notion that immune intervention may have influenced the timing and presentation of leukemia recurrence. Strong indications for the presence of immunological pressure on leukemic AML cells by the emergence of HLA loss variants have been recently reported.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, several of the relapses presented at unusual extramedullary sites, a phenomenon described before in conjunction with DLI. [35][36][37][38][39] Together, these observations are compatible with the notion that immune intervention may have influenced the timing and presentation of leukemia recurrence. Strong indications for the presence of immunological pressure on leukemic AML cells by the emergence of HLA loss variants have been recently reported.…”
Section: Discussionsupporting
confidence: 74%
“…Response rates of 30-50% in relapsed MM patients have been reported. 1,2 Several studies have shown that the novel agents in the treatment of MM bortezomib, thalidomide and lenalidomide, besides their anti-myeloma effect, also have immune-modulating effects that may enhance the graft-versus-myeloma reaction. 3,4 In this retrospective analysis, we evaluated the anti-myeloma effect of bortezomib in combination with DLI in 30 patients with MM relapsed after allo-SCT from two Dutch transplant centres (Nijmegen n ¼ 15 and Utrecht n ¼ 15).…”
mentioning
confidence: 99%
“…In the Vancouver series 5 of 14 patients receiving DLI responded. 21 Zeiser et al 48 reviewed the published myeloma DLI data in 2004. Overall 40-52% responded, with 25% having a CR.…”
Section: Is Allosct the Penultimate Intervention? Post-allosct Therapymentioning
confidence: 99%